Idiopathic Thrombocytopenic Purpura-a Literature Based Review - Shaik Mujahid; Jayanti Mukherjee; Narender Boggula (International Journal of Allied Medical Sciences and Clinical Research, 2023)
Immune thrombocytopenia (ITP) is a syndrome in which platelets become coated with autoantibodies to platelet membrane antigens, resulting in splenic sequestration and phagocytosis by mononuclear macrophages. Immune thrombocytopenic purpura (ITP) is an autoimmune pathology characterized by a low platelet count, purpura, and hemorrhagic episodes caused by antiplatelet autoantibodies. The exclusion typically makes the diagnosis of the known causes of thrombocytopenia. IgG autoantibodies sensitize the circulating platelets. It leads to the accelerated removal of these cells by antigen-presenting cells (macrophages) of the spleen and sometimes the liver or other components of the monocyte-macrophage system. Bone marrow compensates the platelet destruction by increasing platelet production. ITP most often occurs in healthy children and young adults within a few weeks following a viral infection. Certain drugs can also cause immune thrombocytopenia indistinguishable from ITP. The clinical presentation may be acute with severe bleeding, or insidious with slow development with mild or no symptoms. The initial laboratory tests useful at the first visit to predict future diagnosis were erythrocyte count, leukocyte count, anti-glycoprotein (GP) IIb/IIIa antibodies, reticulated platelets, plasma thrombopoietin level. Treatment should be restricted to those patients with moderate or severe thrombocytopenia who are bleeding or at risk of bleeding. It should be limited in duration unless demonstrated that symptomatic thrombocytopenia persists. Patients with mild, asymptomatic thrombocytopenia, discovered incidentally on a routine blood count, should not be treated. We present a case report on ITP and summarize the key points in the diagnosis and management of ITP. An optimized treatment strategy should aim at elevating the platelet counts to a safety level with minimal toxicity and improving patient health-related quality of life, and always needs to be tailored to the patients and disease phases. In this review, we address the concepts of adult ITP diagnosis and management and provide a comprehensive overview of current therapeutic strategies under general and specific situations.